APPLICATION OF SAW TECHNIQUE FOR RESEARCH OF POTENTIAL NEW PARTNERS AGENCY OF ASAHAN DISTRICT STATISTICS CENTER - Novi Silvana Kawila; Elly Rahayu; Fauriatun Helmiah (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The Central Bureau of Statistics is a government agency that serves the public in providing accurate statistical data. Central Bureau of Statistics Every year the Central Bureau of Statistics accepts new partners. Partners who do data processing that has been done on data in the field. In this case, the acceptance of new partner candidates is quite often held to carry out survey and population census activities. The partner acceptance process is less effective because it still uses the manual method, namely the approach between existing partners. So we need a decision support system that can help election performance to be more effective. The basic concept of the Simple Addictive Weighting method is to find a weighted sum of performance ratings for each alternative on all criteria or attributes. The purpose of this research is to build and design a data processing application for prospective new partners at the Central Bureau of Statistics of the Asahan district to get an assessment according to the specified criteria. The results of the research conducted produced the best alternative decision, namely Ruslan Efendi with a score of 0.975 and Yenni Yulistina with a value of 0.95. based on these results can assist the Central Bureau of Statistics in determining the assessment of potential new partners so that they can provide a reference in decision making. In accordance with the criteria required by the Central Bureau of Statistics. Keywords: decision support support system; simple addictive weighting; prospective partners;  information systems. Abstrak: Badan Pusat Statistik merupakan salah satu instansi pemerintah yang melayani masyarakat dalam menyediakan data statistik yang akurat. Badan Pusat Statistik Setiap tahunnya Badan Pusat Statistik menerima mitra baru. Mitra yang melakukan pengolahan data yang sudah dilakukan pada data dilapangan.. Dalam hal ini, penerimaan calon mitra baru cukup sering diadakan untuk menjalankan kegiatan survei dan sensus penduduk. Proses penerimaan mitra ini kurang efektif karena masih menggunakan cara manual, yaitu dan pendekatan antara mitra yang sudah ada sebelumnya. Sehingga dibutuhkan  sebuah sistem pendukung keputusan yang dapat membantu kinerja pemilihan menjadi lebih efektif. Konsep dasar dari metode Simple Addictive Weighting  mencari penjumlahan terbobot dari rating kinerja untuk setiap alternative pada semua kriteria atau  atribut. Tujuan penelitian ini dapat membangun dan  merancang sebuah aplikasi pengolahan data calon mitra baru di Badan Pusat Statistik kabupaten Asahan yang tepat untuk mendapatkan penilaian yang sesuai dengan kriteria yang ditentukan. Hasil dari penelitian yang dilakukan menghasilkan sebuah keputusan alternatif terbaik yaitu Ruslan efendi dengan nilai 0.975 serta Yenni Yulistina dengan nilai 0.95. berdasarkan hasil tersebut dapat membantu pihak Badan Pusat Statistik dalam menentukan penilaian calon mitra baru sehingga dapat memberikan acuan dalam pengambilan keputusan. Sesuai dengan kriteria yang dibutuhkan oleh pihak Badan Pusat Statistik.Kata kunci : sistem pendukung pendukung keputusan; simple addictiv weighting; calon mitra; sistem informasi.